Exploring Knowledge Gaps in Systemic Lupus Erythematosus Among Pre-Clinical Students and Junior Doctors in Medical Faculty - Pratama, Mirza Zaka; Rahman, Perdana Aditya; Wahono, Cesarius Singgih; Handono, Kusworini (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2025)
Understanding knowledge gaps is essential for developing more effective educational interventions that can bridge theory and practice. This study aimed to evaluate knowledge gaps in Systemic Lupus Erythematosus between pre-clinical students and junior doctors at a medical faculty. A cross-sectional study was conducted with 250 participants, divided equally between pre-clinical students and junior doctors (N=125 each). Variables such as gender, educational year, GPA, and study time were analyzed. Knowledge was assessed in five domains: pathophysiology, clinical manifestations, diagnosis, treatment, and complications. Linear regression analysis was used to identify factors associated with mean knowledge scores. No significant differences in gender distribution or study time (p = 0.899, p = 0.633, respectively). However, GPA scores were significantly higher among junior doctors (p < 0.001). Pre-clinical students scored higher than junior doctors in all SLE-related domains. GPA and study time were the strongest predictors of higher scores (Beta = 0.917, p < 0.001; Beta = 0.261, p < 0.001). GPA and study time significantly contributed to SLE knowledge scores, while gender and educational year did not. These findings suggest that academic performance and consistent study habits play critical roles in mastering SLE concepts among medical trainees.